Differential Impact of Extended Criteria Donors After Brain Death or Circulatory Death in Adult Liver Transplantation. Issue 12 (21st September 2020) - Pandya, Keval; Sastry, Vinay; Panlilio, Mara T.; Yip, Terry C. F.; Salimi, Shirin; West, Claire; Virtue, Susan; Wells, Mark; Crawford, Michael; Pulitano, Carlo; Strasser, Simone I.; McCaughan, Geoffrey W.; et al.
Abstract : Using grafts from extended criteria donors (ECDs) and donation after circulatory death (DCD) donors is a strategy to address organ shortage in liver transplantation (LT). We studied the characteristics and outcomes of ECD and DCD grafts. We retrospectively studied consecutive adults who underwent deceased donor LT between 2006 and 2019. ECD was defined using modified Eurotransplant criteria. Our primary outcomes were graft and patient survival. A total of 798 grafts were used for LT, of which 93.1% were donation after brain death (DBD; 59.9% were also ECD) and 6.9% were DCD grafts (49.1% were also ECD). Among DBD graft recipients, donors having >33% liver steatosis or 3 ECD criteria resulted in poorer graft survival. Otherwise ECD graft recipients had similar graft and patient survival compared with non‐ECD graft recipients. DCD graft recipients also had similar patient survival compared with DBD recipients. However, DCD grafts from an ECD appeared to have worse outcomes. DCD graft recipients experienced higher rates of early allograft dysfunction (50.9% versus 24.7%; P < 0.001) and ischemic biliopathy (16.4% versus 1.5%; P < 0.001) compared with DBD graft recipients. Use of DBD grafts from ECDs did not impact outcomes unless there was significant donor steatosis or 3 Eurotransplant criteria were met. DCD graft recipients have similar patient survival compared with DBD graft recipients as long as the donor was not an ECD. We recommend that DBD donors with 3 or more ECD features or >33% steatosis and DCD donors with any ECD features be used with caution in adult LT.